The European Investigation Order Instrument of International Judicial Cooperation in Criminal Matters - Airapetean, Artur; Corsei, Andreea; Stefanoaia, Mariana-Alina (Acta Universitatis Danubius. Juridica, 2021)
The European Order of Inquiry is a court decision issued or validated by a judicial authority in an EU Member State in order to carry out the necessary investigative measures in another EU Member State to gather evidence in criminal matters. It is based on mutual recognition, which means that the executing authority has an obligation to recognize and enforce the application of the other State. Enforcement shall be carried out in the same manner and by the same means as if the investigative measure in question had been ordered by an authority of the executing State. A European investigation order may also be issued to obtain evidence that already exists.